Breaking the spores of ganoderma lucidum by fermentation with lactobacillus plantarum - Chaiyavat Chaiyasut (2018)
Ganoderma lucidum has been utilized in medical field from ancient time. In recent studies, it is found that spores of G. lucidum consists of several bioactive substances which are much abundant than in the fruiting body. A hard sporoderm limits the absorption of these active compounds. Therefore, it is necessary to break down the sporoderm to allow complete absorption. The spore breaking methods which have been developed are physical smashing, ultrasonic, high pressure and enzymes application. A few limitations have come forward; they are low yield, high cost, high technology tools requirement and loss valuable substances during production. In this paper, fermentation of G. lucidum with Lactobacillus plantarum was applied to break down the sporoderm. Scanning electron microscope (SEM) was used to characterize the spores. The broken spores were found on the 3 rd day and complete breaking on the 5 th day of fermentation. Lactic acid, acetic acid and combination of these acids did not cause the spore to break down. This technique is simple, less cost. It can be used to produce fermented juices with the benefit from G. lucidum spores and lactic acid bacteria. Mechanism of spore break down by lactic acid bacteria is further investigated. © 2010 Academic Journals.